Design and Build a Saghai Ball Thrower at the 2019 Indonesian Abu Robot Contest - Setiyabudi, Tri; Aji, Wahyu Sapto (Signal and Image Processing Letters, 2021)
Abu Robocon 2019 will be held in the country of Mongolia with the competition theme "The Great URTUU Spreads Knowledge". The 2019 Indonesian ash robot contest made 2 robots, namely MR 1 (Manual Robot) which is run automatically and MR2 (Automatic Manual). In one of the race sessions there was a section of throwing saghai balls. The parameter that must be achieved is the optimization of the embattlement mechanic by landing a throw on target and getting maximum points. The KRAI 2019 robot thrower uses pneumatics. The wind pressure determines the throwing force of the saghai ball. Angle testing to find out the right angle in order to achieve a good and precise on-target throw. Based on the test results of the pitcher's angle of 500, the ball was thrown 20 times resulting in the robot being able to throw well and the average speed was 4.82 m/s. It can be concluded that the angle of 500 is the right angle to produce a lot of 50 points. Testing with a throwing angle of 600, the ball was thrown 20 times resulting in the robot being able to throw, as well as the average speed produced which was 5.20 m/s. The third test with an angle of 700, the ball was thrown 20 times resulting in the robot being able to throw, as well as the average speed produced which was 6.17 m/s. Testing the angle of 500 is the right angle because it can produce a good throw and produce 50 points.